EFEKTIVITAS KINERJA PEGAWAI DALAM PELAYANAN PEMBUATAN E-KTP PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN POLEWALI MANDAR - Nur Fitrah; Karmila Karmila (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to determine the effectiveness of employee performance towards the service of making E-KTP at the Department of Population and Civil Registry of Polewali Mandar Regency, which is more effective in carrying out service duties at the office and find out what are the inhibiting factors of the service. There are also benefits to the research. Namely, it can provide useful information to all walks of life and provide input for the community so that they can motivate employees when carrying out their duties given by the leader. Then it can be determined the results obtained in carrying out public services Polewali Mandar District Government (DISDUKCAPIL), has not been effective in carrying out its service duties that have been measured from two variables that produce an average value recapitulation of the effectiveness of employee performance is 61.0. The average of E-KTP Services was 38.1, with 65 respondents divided into 30 employees and 35 communities. The inhibiting factor is not an effective service in the current situation pandemic, but the employee has made various efforts more effective than before.